Building Green Discipline, Green Work Environment, and Environmental Purpose to Accelerate Green Performance in the Era of Sustainability - Andy Endra Krisna Krisna; Endang Sungkawati Sungkawati; Sri Hastutik Hastutik (Ekonika : Jurnal Ekonomi Universitas Kadiri, 2026)
Green Human Resources Management (GHRM) is a Human Resources Management approach that emphasizes environmentally friendly practices in the recruitment, training, evaluation, and development of employees. Green Discipline, Green Work Environment, and Green Performance are current topics in GHRM, while Environmental Purpose as a motivation strengthens the mediation pathway. The purpose of this study is to find out how work behavior consisting of Green Discipline, Green Work Environment, and Environmental Purpose can improve Green Performance while supporting the principles of Green Human Resources. The research method used is a quantitative approach, with 183 employees of PT. Indolakto East Java as the research object. Data collection was conducted through questionnaires. The analysis techniques used is Structural Equation Modeling (SEM). The Results of this study prove that a model that integrates Green Discipline, Green Work Environment, and Environmental Purpose is a comprehensive approach to encourage Green Performance.